2020
DOI: 10.1037/neu0000693
|View full text |Cite
|
Sign up to set email alerts
|

Everyday discrimination and subsequent cognitive abilities across five domains.

Abstract: Objective: Previous research suggests that everyday discrimination is associated with worse concomitant performance in several cognitive domains, as well as faster subsequent declines in episodic memory. This study aimed to extend knowledge on the specificity, durability, and mechanisms of associations between everyday discrimination and cognition by using a comprehensive neuropsychological battery and a longitudinal mediation design. Method: Participants included 3,304 older adults in the Health and Retiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 51 publications
(65 reference statements)
1
40
0
Order By: Relevance
“…Cognition was operationalized by using five-factor scores obtained from a published confirmatory factor analysis (CFA) of the HCAP neuropsychological battery (Zahodne et al, 2020). Factor scores indexed the following domains: episodic memory, executive function, visuoconstruction, processing speed, and language.…”
Section: Methodsmentioning
confidence: 99%
“…Cognition was operationalized by using five-factor scores obtained from a published confirmatory factor analysis (CFA) of the HCAP neuropsychological battery (Zahodne et al, 2020). Factor scores indexed the following domains: episodic memory, executive function, visuoconstruction, processing speed, and language.…”
Section: Methodsmentioning
confidence: 99%
“…That is due to its continuity, identity-relatedness, and the fact it is enacted by a member representing a dominant influential Group than yours or a powerful institution, such as the police (or the powerful family for the child). Further, longitudinal research (Barnes et al, 2012; Zahodne et al, 2020) found that everyday discrimination is associated with worse cognitive functioning in multiple domains that included executive functioning, processing speed, and visuoconstruction.…”
Section: Interdependence Stressors and Traumasmentioning
confidence: 99%
“…In recognition of such pathways, Zuelsdorff et al 57 . and others 58,59 have investigated stress and cognition in racially diverse cohorts. Those studies examining late‐life stress in Black elders found that disproportionately high stress exposure partially explains racial disparities in cognitive health 57,58 …”
Section: Understanding Race and Racialization With The Health Dispari...mentioning
confidence: 99%